2006
DOI: 10.1614/ws-06-097r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Horseweed (Conyza canadensis) seed collected in the planetary boundary layer

Abstract: Horseweed is a winter or summer annual plant, native to North America and distributed worldwide in temperate climates. This plant is considered an important agricultural weed because it can reduce agricultural yields by 90% at high densities and becomes problematic under low-tillage agriculture. Seed production is robust with an estimated 200,000 seeds produced per plant, and seed dispersal is wind-assisted. The confirmation of glyphosate-resistant horseweed in Delaware in 2001 and the rapid spread of the resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 18 publications
1
118
0
5
Order By: Relevance
“…Our results suggested that the natural extracts of C. canadensis have the potential to inhibit the germination and growth of competing plants in the field. The potential allelopathic effects could contribute to the invasion success of C. canadensis in its introduced ranges, and its success cannot just be attributed to a single trait, such as the huge production of wind-dispersed seeds (Bhowmik & Bekech, 1993;Shields et al, 2006;Main et al, 2006). Interestingly, the aqueous extracts of C. canadensis at all concentrations had no significant effect on its own the germination and shoot length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggested that the natural extracts of C. canadensis have the potential to inhibit the germination and growth of competing plants in the field. The potential allelopathic effects could contribute to the invasion success of C. canadensis in its introduced ranges, and its success cannot just be attributed to a single trait, such as the huge production of wind-dispersed seeds (Bhowmik & Bekech, 1993;Shields et al, 2006;Main et al, 2006). Interestingly, the aqueous extracts of C. canadensis at all concentrations had no significant effect on its own the germination and shoot length.…”
Section: Discussionmentioning
confidence: 99%
“…(Main et al, 2006). It is considered an important agricultural weed because it can reduce agricultural yields by 90% at high densities (100-200 plants m -2 ) (Shields et al, 2006). Seed production is robust with an estimated 100,000 wind-dispersed seeds produced per plant when densities reached 200 plants m -2 and 200,000 seeds when plant densities were low (10 plants m -2 ) (Bhowmik & Bekech, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Autogamous, a single horseweed plant may produce well over 200,000 seeds. The small seeds have pappi that enable wind and water dispersal (Bhowmik and Bekech, 1993;Weaver 2001) to sometimes very long distances (DeVlaming and Proctor, 1968;Weaver and McWilliams, 1980;Andersen, 1993;Dauer et al, 2006;Shields et al, 2006). Moreover, horseweed seeds are not dormant and can germinate immediately after maturity in the fall, spring, or midsummer (Bhowmik and Bekech, 1993;Weaver, 2001).…”
mentioning
confidence: 99%
“…and Conyza spp. is very important since they are prolific seed producers, with a single plant capable of producing thousands of non-dormant seeds (Weaver 2001, Travlos andChachalis 2012), which can be widely dispersed by wind (Shields et al 2006). Efficacy data presented at 60 DAT for S. oleraceous, C. canadensis and S. media reveal that S. media was relatively easier to control with most herbicides (Table 5).…”
Section: Resultsmentioning
confidence: 99%